KOMUNIKASI PENYULUHAN SATUAN LALU LINTAS POLRESTA DALAM PROGRAM POLISI SAHABAT ANAK PADA TAMAN KANAK-KANAK DI KOTA PEKANBARU - Febriyanti, Putri Trisna; Awza, Rusmadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Child friendly police program is an extension program for kindergartens carried out by the Polresta Traffic Unit Pekanbaru, to provide early childhood knowledge about traffic symbols and also make children not afraid of the police profession, attitudes and actions must be taught early on so that it becomes a habit to be able to maintain traffic safety. One of the efforts that was carried out by the Pekanbaru week by carrying out a police program of child friends in early childhood. Counseling is carried out by providing material to schoolchildren so that they can apply the orderly behaviour that has been taught. This study aims to determine the selection of communicators, messages, media, targets, and effects of unit extension communication an Traffic Police in a child friend Police program in kindergarten in Pekanbaru City.The research method used in this study is a qualitative research method. This qualitative research aims to explain the phenomenon as deeply as possible through data collection. Using a purposive technique by interviewing 12 informants who participated in the police program of child friends in kindergartens carried out by the Pekanbaru police traffic unit.The results of the study show that the communicator of the unit unit is know as the National Traffic Unit selected based on those who have was credibility, expertise and sincerity as communicators who can motivate the importance of traffic discipline to early childhood in the city of Pekanbaru. The messages conveyed in the form of informative and persuasive. By giving material about the symbols of traffic and helmet use properly. In the delivery of messages the Dikyasa also uses supporting tools. The media used are children’s helmets, traffic symbols, microphones, banners. Target activities include early childhood, namely kingergartens and paud. And the effect of childres are good at commenting on the wrong person, and the cognitive, affective, and conative levels.